Cloning, characterisation and expression of the SERPINB14 gene, and association of promoter polymorphisms with egg quality traits in layer chicken. Issue 6 (2nd November 2021) - Kanaka, K. K.; Chatterjee, R. N.; Kumar, P.; Bhushan, B.; Divya, D.; Bhattacharya, T. K.
ABSTRACT: 1. Ovalbumin (SERPINB14) is the most abundant protein present in egg white contributing about 54% of the total egg protein. In this study, the objectives were to clone and characterise the coding sequence of the SERPINB14 gene, to explore its expression profile, identify polymorphisms in the promoter of the gene and explore any association with egg quality traits in White Leghorn chickens. 2. SNPs and mRNA expression of SERPINB14 in White Leghorn chicken lines were detected by PCR-single strand conformation polymorphism (SSCP) along with sequencing and qPCR. The open reading frame (ORF) was cloned in an expression plasmid vector and sequenced. 3. The ORF of this gene was 1161 bp encoding a peptide of 386 amino acids. There were three SNPs observed in the coding region of the gene, one of which was of the mis-sense type, having c562G>A transition which resulted in substitution of alanine to threonine at position 188 in the protein sequence. In both the lines, an increase in expression of the gene was observed after onset of egg production with peak expression at the 40 th week of age compared to before onset of lay. The SERPINB14 gene was expressed in the magnum, but not in ovary and infundibulum, tissues of each White Leghorn line. The promoter region of the gene showed SNPs with three haplotypes; H1, H2, and H3. The haplo groups were associated with the egg weight and age at sexual maturity in the IWI line and Haugh unit and albumin index in the IWK line. 4. It was concluded that the ORF of SERPINB14 gene in White Leghorn chicken lines is polymorphic. The promoter region of the gene is also polymorphic and has significant (P < 0.05) association with Haugh unit and egg weight in IWK and IWI chicken lines, respectively.